Editorial - Holger Pötzsch; Kristine Jørgensen (Eludamos)
The editorial argues for the necessity of thinking and acting critically in times of multiple crises. Then it introduces the contributions brought together in the present issue and, finally, takes up some internal issues as Eludamos.